Groundwater Arsenic Contamination and Health Implications among Urban Slum Communities along the Padma Riverbank, Rajshahi, Bangladesh - Shafiuzzaman S.M.; Yasmin Zakiya; Mohammad Nur Golam (International Journal of Recent Trends in Multidisciplinary Research, 2026)
Groundwater is a major source of drinking water in Bangladesh, particularly among low-income and slum communities, but naturally occurring arsenic contamination poses a significant public health concern. This study assessed the physicochemical quality of groundwater and its potential health implications among residents of selected urban slum communities in Rajshahi City Corporation. A cross-sectional mixed-methods approach was employed, integrating household surveys, field observations, and laboratory analysis of 16 groundwater samples collected from nine wards (Wards 1, 4, 7, 22, 23, 24, 25, 28, and 29). Groundwater samples were analysed for arsenic, total dissolved solids (TDS), and salinity, while household questionnaires were used to document water-use practices, awareness, and self-reported health conditions. Arsenic concentrations showed substantial spatial variation, ranging from relatively low levels to a maximum of approximately 0.064 mg/L. Four samples (GW-10, GW-11, GW-12, and GW-13; 25%) exceeded the WHO guideline value of 0.01 mg/L, while GW-10 also exceeded the Bangladesh national permissible limit of 0.05 mg/L. Ward-level variation further demonstrated localised contamination hotspots. Elevated TDS and salinity were also observed in several samples, indicating variability in groundwater mineralisation and overall water quality. The household survey revealed considerable prevalence of reported water-related health conditions, including gastrointestinal disorders (84.21%), diarrhoea (82.11%), dysentery (62.11%), respiratory problems (54.74%), and several dermatological conditions, with fungal infections (28.42%) being the most frequently reported skin problem. Although these self-reported health outcomes cannot establish a causal relationship with arsenic exposure, their coexistence with contaminated groundwater indicates a potential public health concern. The findings demonstrate that groundwater quality in the urban slum communities of Rajshahi is spatially heterogeneous and that localised arsenic contamination remains a significant risk. Regular well-specific monitoring, arsenic screening, provision of safe alternative water sources, community awareness, and targeted mitigation measures are recommended to reduce long-term exposure and protect vulnerable urban populations.